Carpaine modulates calcium mobilization through PLC-InsP3 pathway in cardiomyocyte - Nur Syafinaz Wasli; Eleanor Joanne Muyou; Suhaini Sudi; Fong, Siat Yee; Caroline Sunggip (Malaysian Society for Molecular Biology and Biotechnology (MSMBB), 2025)
Carpaine, an alkaloid found in the leaves of Carica papaya (papaya), is known for its diverse pharmacological properties. A previous study demonstrated that carpaine promotes cell proliferation and repair of H9c2 cardiomyocytes after oxidative insults. However, the exact mechanism of action remains elusive. Calcium (Ca2+) is the most versatile and universal signalling agent modulating essential physiological functions. This study aims to decipher the calcium modulation of carpaine extracted from C. papaya leaves. Carpaine was isolated from C. papaya leaves, and nuclear magnetic resonance (NMR) spectroscopy confirmed the extracted alkaloid's purity. The 50% inhibitory concentration (IC50) of carpaine in cardiomyocytes was determined using an MTT assay. Fluorescence-based assays were used to determine intracellular Ca2+ mobilization. Pyrazole-3-carboxylic Acid (Pyr3), U71322, and Xestospongin C (Xest C), which are the inhibitors of TRPC3/6, Phospholipase C and the InsP3 receptor, respectively, were used to explore the mode of calcium mobilization in cardiomyocytes. Carpaine induced a significant increase in Ca2+ mobilization into cardiomyocyte cells. Inhibition of PLC or TRPC3 significantly suppresses the Ca2+ mobilization, but interestingly, the inhibition of the InsP3 receptor alone nearly abolished the carpaine-induced Ca2+ mobilization. These findings suggest that carpaine induces a calcium store-dependent intracellular Ca2+ mobilization in cardiomyocytes.